No-additive salting-out liquid-liquid extraction-A tool for purification of positively charged compounds from highly salted reaction mixtures - Moravcová, Dana; Čmelík, Richard; Křenková, Jana (Journal of separation science, 2020)
A novel and original application of salting-out assisted liquid-liquid extraction is presented. This technique was used to purify the final reaction products (quaternary ammonium salts) from unreacted components and by-products present in multiple excesses. The partition of two structurally related compounds as (2-aminoethyl)trimethylammonium salt (a labeling reagent) and a derivative of [2-(imidazoline-1-yl)ethyl]trimethylammonium salt (a final reaction product of N-acetylglucosamine labeling by (2-aminoethyl)trimethylammonium salt) between acetonitrile-rich and water-rich layers was monitored by hydrophilic interaction chromatography with electrospray ionization mass spectrometry. Despite the poor solubility of both highly polar substances in solutions containing a high concentration of acetonitrile, the main portion of the labeling reagent (72%) can be removed from the crude reaction mixture in the first extraction step using 95% acetonitrile/5% water as an extraction solvent. The purified final reaction product contained only 2% of the labeling reagent, and it was suitable for analysis by direct infusion mass spectrometry to confirm its identity. The capability of the suggested purification protocol to process small-volume highly salted reaction mixtures was also proven by analysis of saccharide mixture containing glucose, maltose, and maltotriose labeled by the positively charged tag.